2013
DOI: 10.1002/ejoc.201300840
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Benign Lewis Acid Promoted [2+3] Dipolar Cycloaddition Reactions of Nitrile Imines with Alkenes in Water

Abstract: Mild and environmentally benign Lewis acid promoted 1,3-dipolar cycloaddition reactions of α-hydrazonyl chlorides with alkenes in water are reported. These α-hydrazonyl chlorides, in the presence of Lewis acids, generate nitrile imines in situ which react with dipolarophiles to furnish the corresponding cycloaddition products. In many cases, the required times for the completion of the Lewis acid promoted 1,3-dipolar cycloaddition reactions in water were comparable to the equivalent reactions performed in an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 77 publications
0
9
0
Order By: Relevance
“…It is possible to generate spiro-pyrazolines by reacting hydrazonyl chlorides with alkenes in the presence of a stoichiometric amount of CuSO 4 in pure water at room temperature. 83 Among the various Lewis acids that were tested, CuSO 4 is one of the most efficient (eq 56). It is possible to synthesize quinoline-4-carboxylic acid derivatives by a CuSO 4 -catalyzed Pfitzinger reaction.…”
Section: Martin Pichette Drapeau and Thierry Ollevier Université Lavalmentioning
confidence: 99%
“…It is possible to generate spiro-pyrazolines by reacting hydrazonyl chlorides with alkenes in the presence of a stoichiometric amount of CuSO 4 in pure water at room temperature. 83 Among the various Lewis acids that were tested, CuSO 4 is one of the most efficient (eq 56). It is possible to synthesize quinoline-4-carboxylic acid derivatives by a CuSO 4 -catalyzed Pfitzinger reaction.…”
Section: Martin Pichette Drapeau and Thierry Ollevier Université Lavalmentioning
confidence: 99%
“…5,6d,7g,13,14 In addition to methodology development, we are also equally interested in assessing structural and biological applications for spiro-pyrazolines. Recently, we demonstrated the construction of 1,3,5-trisubstituted pyrazoles on the basis of the 1,3-dipolar cycloaddition protocol, which was then followed by an unforeseen ring fragmentation/elimination.…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of a base, hydrazonoyl chlorides convert into nitrilimines, which are highly reactive 1,3‐dipoles [2] and participate in 1,3‐dipolar cycloaddition reactions with a variety of dipolarophiles such as alkenes, alkynes, carbonyls, thiocarbonyls, nitriles etc ., to give five membered azaheterocycles as shown in Scheme 1. In literature, however, similar 1,3‐dipolar cycloaddition reactions of nitrilimines are also known under acid catalysis and the examples are: i) synthesis of spiropyrazoles by reaction of nitrilimines with alkenes under copper nitrate catalysis [3] and ii) Preparation of dihydropyrazoles by reaction of nitrilimines with alkenes using magnesium bis(trifluoromethanesulfonimide) as a catalyst [4] . In both these reactions, alkenes are dipolarophiles and similar studies with other dipolarophiles such as C=S under acid catalysis are so far not reported in literature.…”
Section: Methodsmentioning
confidence: 99%